DNA and Protein-Based Methods for Halal Gelatin Authentication: A Review - Nurul Azizah; Welly Anggraini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Tracing and tracking halal has emerged as an imperative for Muslim consumers worldwide to ensure that the meat-based products comply with Islamic law and food safety standards. The most challenging technical issue in halal authentication concerns products derived from gelatin. Because extreme manufacturing processes, such as high-temperature and chemical processing, damage the physical and molecular architecture of raw materials, detection is difficult. Objective: This study builds on a systematic literature review with a PRISMA protocol to map DNA- and protein-based detection techniques and compare their efficiencies. Methods: A systematic search was conducted across major databases, including Google Scholar, ScienceDirect, and ResearchGate, for peer-reviewed articles published from 2015 to 2025. From this process, 25 studies with high-impact potential were selected for thematic analysis. The results show that DNA-based methods dominate the literature (80%). Despite this, quantitative PCR (qPCR) remains the